MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA MELALUI METODE DISKUSI KELOMPOK: LITERATURE REVIEW - Halimatus Sa’diyah; Robitotul Islamiah; Laksmi Evasufi Widi Fajari (Journal of Professional Elementary Education, 2022)
This article is a literature review study that aims to determine the importance of applying the group discussion method in improving students critical thinking skills. Students' critical thinking skills must be developed in the learning process by applying various learning methods that are able to support students' reasoning thinking processes, one of which is the group discussion method. The application of the group discussion method requires students to think analytically and scientifically, as well as encourage opinion polls. The purpose of this article review is to describe the application of the group discussion learning method and the characteristics of students' critical thinking skills. The steps that can be applied in using the group discussion method in the learning process in improving critical thinking skills include: 1) Delivering the introduction, objectives, and setting settings, 2) Directing the discussion, 3) Organizing a discussion, 4) Ending the discussion, 5) Doing question and answer